2022
DOI: 10.3390/ma15165615
|View full text |Cite
|
Sign up to set email alerts
|

Pellet-Based Fused Filament Fabrication (FFF)-Derived Process for the Development of Polylactic Acid/Hydroxyapatite Scaffolds Dedicated to Bone Regeneration

Abstract: Scaffolds can be defined as 3D architectures with specific features (surface properties, porosity, rigidity, biodegradability, etc.) that help cells to attach, proliferate, and to differentiate into specific lineage. For bone regeneration, rather high mechanical properties are required. That is why polylactic acid (PLA) and PLA/hydroxyapatite (HA) scaffolds (10 wt.%) were produced by a peculiar fused filament fabrication (FFF)-derived process. The effect of the addition of HA particles in the scaffolds was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…This is in contrast to the results presented by Bayart et al ; there the viability and the growth of hDPSC were decreased for PLA in presence of HAp compared to pure PLA scaffolds. 24 Similar results, as obtained in our study, were reported by Babilotte et al : printed scaffolds of PLGA vs. PLGA-nano-HAp composite were seeded with human adipose-derived stem cells (hADSC) as well as with human bone-marrow stromal cells (hMSC) and during cultivation, no significant differences in viability and metabolic activity between the two material groups were observed. 18 Roh et al fabricated porous scaffolds by 3D extrusion-printing of PLGA and composites of PLGA, nano-HAp and β-TCP (10 wt% each); after seeding with the osteoblast-like cell line MC3T3-E1, they observed a significantly enhanced cell viability on the composite vs. the pure polymer scaffolds.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in contrast to the results presented by Bayart et al ; there the viability and the growth of hDPSC were decreased for PLA in presence of HAp compared to pure PLA scaffolds. 24 Similar results, as obtained in our study, were reported by Babilotte et al : printed scaffolds of PLGA vs. PLGA-nano-HAp composite were seeded with human adipose-derived stem cells (hADSC) as well as with human bone-marrow stromal cells (hMSC) and during cultivation, no significant differences in viability and metabolic activity between the two material groups were observed. 18 Roh et al fabricated porous scaffolds by 3D extrusion-printing of PLGA and composites of PLGA, nano-HAp and β-TCP (10 wt% each); after seeding with the osteoblast-like cell line MC3T3-E1, they observed a significantly enhanced cell viability on the composite vs. the pure polymer scaffolds.…”
Section: Discussionsupporting
confidence: 92%
“…The same effect was observed by Bayart et al , who printed PLA and PLA-HAp (ratio 90 : 10) composite scaffolds using the same printing method as in the present study. 24 The authors showed that the contact angle between both materials appeared the same but that the swelling was significantly stronger in presence of HAp which was attributed to the higher hydrophilicity of the mineral itself. Further, we observed that dissolving filler materials have led to micropores in the 3D structure visible in the SEM images, Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This shows that the synthetic scaffolds we used had a similar tissue response and may have a tissue integration profile as the autografts [ 48 ]. The results presented in this paper shall encourage further scientific research and, in perspective, translational studies in animals and later in humans so that this biocompatible scaffold can be developed to fill bone defects [ 22 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 97%
“…The APF method can process thermoplastic materials by combining injection molding and 3D-printing technology. The following literature describes the APF and parameter optimization process [17]- [19]. The material of choice was composite Resomer® LR 706 S (Evonik Operations GmbH, Darmstadt, Germany), comprising 70% Poly(-L-lactide-co-D,L-lactide) 70:30 (PLDLLA) and 30% β-Tricalcium Phosphate (β-TCP).…”
Section: Manufacturing Processmentioning
confidence: 99%